2018
DOI: 10.1111/jdv.14913
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in itch and other psoriasis symptoms with brodalumab in phase 3 randomized controlled trials

Abstract: Brodalumab demonstrated rapid, robust improvements in symptoms assessed by the PSI, including itch, vs. placebo and ustekinumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
(74 reference statements)
1
17
0
Order By: Relevance
“…Pruritus-reducing effects of biologic treatment on psoriatic pruritus have been reported (393)(394)(395)(396)(397)(398)(399)(400)(401). One single report of cases referred to persistent CP (402).…”
Section: 411mentioning
confidence: 99%
“…Pruritus-reducing effects of biologic treatment on psoriatic pruritus have been reported (393)(394)(395)(396)(397)(398)(399)(400)(401). One single report of cases referred to persistent CP (402).…”
Section: 411mentioning
confidence: 99%
“…When reporting the PSI, patients rate the itch during the previous 24 hours from 0 (not at all) to 4 (very severe). Gottlieb and colleagues13 analysed PSI itch scores from across AMAGINE-1/-2/-3 and reported that this improved with brodalumab 140 and 210 mg doses, starting at week 2 and sustained through week 12. The PSI itch response associated with brodalumab 210 mg was greater than that of ustekinumab through to week 12, and at week 52 for patients who remained on constant treatment with either therapy after re-randomisation 13…”
Section: Brodalumab Clinical Efficacy Datamentioning
confidence: 99%
“…The PSI total score is the sum of the eight items and can range from 0 to 32. Assessment and validation of the PSI have shown strong internal consistency, test-retest reliability and responsiveness to changes in clinical studies [13,15].…”
Section: Introductionmentioning
confidence: 99%